2013
DOI: 10.1111/sjop.12059
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of poly‐victimization in Chinese adolescents

Abstract: Multiple types of victimization or poly-victimization (PV) can occur simultaneously during childhood, resulting in outcomes that are detrimental and difficult to reverse. Very few studies have focused on PV in Chinese adolescents. The present study is based on information collected from a stratified cluster sample of 1,561 females and 1,594 males aged 12-18 years living in Shandong Province, China. A self-administered questionnaire was used to assess background information, the Juvenile Victimization Questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
51
5
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 41 publications
9
51
5
2
Order By: Relevance
“…Girls exposed to two or more types of maltreatment had 4.1 times the odds of major depression compared to girls not exposed, adjusting for confounding variables. Similarly, other studies have also found levels of depression in females increase significantly following poly-maltreatment (Cisler et al, 2012, Dong et al, 2013, du Plessis et al, 2015; Finkelhor et al, 2009; Richmond et al, 2009; Sundermann et al, 2013; Turner et al, 2006). Hence, although different forms of maltreatment often co-exist, it appears they can make unique additional contributions towards increased risk for depression.…”
Section: Discussionsupporting
confidence: 52%
“…Girls exposed to two or more types of maltreatment had 4.1 times the odds of major depression compared to girls not exposed, adjusting for confounding variables. Similarly, other studies have also found levels of depression in females increase significantly following poly-maltreatment (Cisler et al, 2012, Dong et al, 2013, du Plessis et al, 2015; Finkelhor et al, 2009; Richmond et al, 2009; Sundermann et al, 2013; Turner et al, 2006). Hence, although different forms of maltreatment often co-exist, it appears they can make unique additional contributions towards increased risk for depression.…”
Section: Discussionsupporting
confidence: 52%
“…Many children and adolescents get involved in bullying as bullies or victims at some time during their years of study at the school (Dong, Cao, Cheng, Cui, & Li, 2013;Wei, Chang, & Chen, 2016;Liu, Chen, Hu, Guo, & Xiao, 2017;García & De Paúl Ochotorena, 2017). However, gender differences in bullying and victimization seem to be different from one country to another and from one sample to another.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In low and middle income countries (LMICs) such as South Africa and Jamaica, lifetime exposure to at least one form of violence is considerably higher and experienced by almost every child in the samples in these countries (Kaminer, du Plessis, Hardy & Benjamin, 2013;SammsVaughan, Jackson & Ashley, 2005;Samms-Vaughan, in press). However, in some LMICs such as China, the prevalence of exposure to violence is relatively low (Dong, Cao, Cheng, Cui, & Li, 2013). Lifetime polyvictims are defined as the top 10% of those who had multiple experiences of violence, and past year polyvcitims as those who had more than four different exposures (Finkelhor et al, 2009).…”
mentioning
confidence: 99%